در گزينهٔ «2» داريم:
$P((A-B)\left| A \right.)=\frac{P((A-B)\bigcap A)}{P(A)}=\frac{P(A-B)}{P(A)}$
$=\frac{P(A)-P(A\bigcap B)}{P(A)}=1-\frac{P(A\bigcap B)}{P(A)}$
$\xrightarrow{P(B\left| A \right.)=\frac{P(A\bigcap B)}{P(A)}}=1-P(B\left| A \right.)=1-\frac{1}{3}=\frac{2}{3}$
تشريح گزينههای ديگر:
$1)P((A-B)\left| B \right.)=\frac{P((A-B)\bigcap B)}{P(B)}=\frac{P(\varnothing )}{P(B)}=\frac{0}{P(B)}=0$
$3)P(A\left| (B-A))=\frac{P(A\bigcap (B-A))}{P(B-A)}=\frac{P(\varnothing )}{P(B-A)} \right.=\frac{0}{P(B-A)}=0$
$4)P(A\left| (A-B))=\frac{P(A\bigcap (A-B))}{P(A-B)} \right.=\frac{P(A-B)}{P(A-B)}=1$